Political and Cognitive Structures Underlying Scientific Inquiry in the University: The Challenge to Educational Researchers - Dumont, Florent; Lecomte, Conrad (Canadian Journal of Higher Education, 1985)
There is a disabling avalanche of scientific production which has overtaken most students of the behavioral sciences. Though science is advanced by this production, much of it is seen to be of marginal value. This has caused some disenchantment among university students with psychology-based research. To understand the sources of this problem, several phenomena are re-examined: (a) the functional autonomy of research paradigms and their assumptive justifica- tions, (b) the failure to discard them when their dysfunction interferes with inquiry directed to solving pressing social problems, and (c) the intersection of politics, academic policies, and the reward structures woven into publication and research networks. The challenge to university researchers, among others, that these conditions impose, are assessed, and suggestions for countering them are presented.